1983
DOI: 10.1152/ajpregu.1983.244.3.r356
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic hagfish cardiac muscle: metabolic basis of tolerance to anoxia

Abstract: Oxygen tensions in the major venous inputs to the systemic and portal-vein hearts of normoxic Atlantic hagfish (12.3 +/- 1.7 and 11.0 +/- 1.6 mmHg, respectively) are low compared with typical vertebrate values. Anoxia and poisoning with cyanide and azide do not significantly affect in situ performance of the systemic heart. Idoacetate poisoning, however, results in a significant decrease in cardiac performance of the systemic heart to 12% of the initial value after 3 h. Activities of mitochondrial enzymes of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
2
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 14 publications
4
57
2
1
Order By: Relevance
“…This is done via modulation of catecholamine release from chromaffin tissue located within the cardiac chambers themselves (Euler and Fänge, 1961;Bloom et al, 1963;Perry et al, 1993;Axelsson et al, 1990;Farrell, 2007). A tonic β-adrenergic stimulation of the hagfish heart is consistent with the bradycardic effects of sotalol in vivo (Hansen and Sidell, 1983;Axelsson et al, 1990) and nadolol in vitro ( present study). Production and recycling of catecholamines involves the ratelimiting conversion of tyrosine to 3,4-dihydroxyphenylalanine, which requires oxygen (Levitt et al, 1965).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This is done via modulation of catecholamine release from chromaffin tissue located within the cardiac chambers themselves (Euler and Fänge, 1961;Bloom et al, 1963;Perry et al, 1993;Axelsson et al, 1990;Farrell, 2007). A tonic β-adrenergic stimulation of the hagfish heart is consistent with the bradycardic effects of sotalol in vivo (Hansen and Sidell, 1983;Axelsson et al, 1990) and nadolol in vitro ( present study). Production and recycling of catecholamines involves the ratelimiting conversion of tyrosine to 3,4-dihydroxyphenylalanine, which requires oxygen (Levitt et al, 1965).…”
Section: Discussionsupporting
confidence: 71%
“…Beyond their basal position in vertebrate evolution, hagfishes are biologically intriguing because of their anoxia tolerance and their legendary ability to produce copious amounts of slime (Hansen and Sidell, 1983;Stecyk and Farrell, 2006;Cox et al, 2010;Herr et al, 2010). More recently, hagfish have been proposed as champions of CO 2 tolerance (Baker et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crude homogenates were prepared and CS activity was determined by the reduction of 5,5′-dithiobis(2-nitrobenzoic acid) (DTNB) and the resulting change in absorbance at 412·nm using a Perkin-Elmer Lamda 6 spectrophotometer (Norwalk, CT, USA). The reaction mixture contained 0.4·mmol·l -1 acetyl CoA, 0.25·mmol·l -1 DTNB, 0.5·mmol·l -1 oxaloacetate and 50·mmol·l -1 imidazole, pH·7.83 (Hansen and Sidell, 1983). Reactions were conducted at 25°C.…”
Section: Citrate Synthase (Cs) Assaysmentioning
confidence: 99%
“…By contrast, experimental evidence indicates that the hearts of teleost fish function aerobically (Driedzic, 1983;Driedzic et al 1983: Farrellefa, 1985. The anoxic tolerance of the heart of the Atlantic hagfish Myxine glutinosa has been demonstrated in vitro (Rybak and Boivinet, 1959), together with its dependence upon glycolysis for the supply of energy (Rybak, 1959;Hansen and Sidell, 1983). Recently it has been shown that M. glutinosa can maintain cardiac output in vivo T even during severe environmental hypoxia (Axelsson et al 1990).…”
Section: Introductionmentioning
confidence: 99%